(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
Halima Khudoyberdiyeva is one of the most remarkable Uzbek poets who skillfully combined national spirit, feminine sensitivity, and artistic expressiveness in her works. The stylistic devices used in her poems — alliteration, personification, repetition, epithets, and metaphors — play a crucial role in revealing the depth of the female soul, the warmth of maternal love, and the sincerity of patriotic feelings